2022
DOI: 10.3233/cbm-210455
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and prognostic effect of ABO blood group on immune checkpoint inhibitors

Abstract: BACKGROUND: The relationship of the ABO blood group system with the immune response is known, but its relationship with immune checkpoint inhibitors (ICIs) has not been clearly investigated until now. OBJECTIVE: In this study, the relationship between different blood groups and nivolumab treatment response in patients with advanced malignant melanoma was investigated. METHODS: The data of patients who used nivolumab for advanced malignant melanoma between April 2018 and April 2021 were retrospectively reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…It is also found that the efficacy of immune checkpoint inhibitors (ICIs) could be influenced by the ABO blood group, and advanced malignant melanoma patients with type B or AB had significantly longer overall survival (OS) than other blood types after using ICIs. 52 Similar findings have been found in other blood group systems. For example, CD44, which is identical to the blood group antigen In b, is associated with lymphocyte (T cell) activation, hematopoietic development, and metastasis of malignant lymphoma.…”
Section: Methodssupporting
confidence: 82%
“…It is also found that the efficacy of immune checkpoint inhibitors (ICIs) could be influenced by the ABO blood group, and advanced malignant melanoma patients with type B or AB had significantly longer overall survival (OS) than other blood types after using ICIs. 52 Similar findings have been found in other blood group systems. For example, CD44, which is identical to the blood group antigen In b, is associated with lymphocyte (T cell) activation, hematopoietic development, and metastasis of malignant lymphoma.…”
Section: Methodssupporting
confidence: 82%
“…Furthermore, it is worth considering that by combining rs659104 into the haplotype analysis, certain patient populations with an extended OS and PFS after ICI treatment could be identified. Additionally, a study involving 73 patients with advanced melanoma highlighted the significant advantage of antigen B presence on survival 32 . Discrepancies in cancer types (only one melanoma case in the current study), sample size, and research ethnicity might contribute to the differing results.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, a study involving 73 patients with advanced melanoma highlighted the significant advantage of antigen B presence on survival. 32 Discrepancies in cancer types (only one melanoma case in the current study), sample size, and research ethnicity might contribute to the differing results.…”
Section: Discussionmentioning
confidence: 83%
“…In that study, we investigated the predictive and prognostic effects of the ABO blood group in patients using nivolumab as a single agent in advanced melanoma. 8 In patients with melanoma, the longest PFS and the longest OS were observed in patients with blood group B (16.1 and 20.3 months for PFS and OS, respectively). However, a comparison of the 4 arms showed no significant difference.…”
Section: Discussionmentioning
confidence: 90%
“…In that study, the survival and response rates were found to be better with ICI treatment in patients with the B antigen. 8 In this study, we investigated the predictive and prognostic value of the ABO blood group system in patients who were administered ICIs for treating advanced RCC. This is the first study conducted on patients with RCC.…”
mentioning
confidence: 99%